Aquaporins: A new target for traditional Chinese medicine in the treatment of digestive system diseases - Huang, Yuchan; Yan, Shidu; Su, Zixia; Xia, Lei; Xie, Jinling; Zhang, Fan; Du, Zhengcai; Hou, Xiaotao; Deng, Jiagang; Hao, Erwei (Frontiers in Pharmacology, 2022)
AQPs are key proteins that protect the gastrointestinal tract from pathogenic factors such as Helicobacter pylori and cancer cells. AQP regulators can prevent and treat most gastrointestinal-related diseases, such as colorectal cancer, gastric ulcer, and gastric fundic gland polyps. Many studies have shown that the abnormal expression of AQPs is associated with gastrointestinal, skin, liver, kidneys, edema, cancer, and other diseases. Although recent studies have proposed clinically relevant AQP-targeted therapies, such as the development of AQP inhibitors, clinical trials are still lacking and there are many difficulties. Traditional Chinese medicine (TCM) has been used in China for thousands of years to prevent, treat and diagnose diseases, which is under the guidance of traditional Chinese medical theory. Herein, we review the latest research on the regulation of AQPs by TCMs and their active ingredients, including Rhei Radix et Rhizoma, Atractylodes macrocephala, Salviae miltiorrhizae Radix et Rhizoma, Poria, Astragali radix, and other 26 TCMs, as well as active ingredients. Among them, the active ingredients include anthraquinones, saponins, polysaccharides, and flavonoid glycosides. Through our review and discussion of numerous studies, we attempt to explore the regulatory effects of TCMs and their active ingredients on AQP in the corresponding parts of the body in terms of the triple energizer in Chinese medicine: “ upper energizer, middle energizer, and lower energizer ”, which may offer unique opportunities for the development of AQP-related therapeutic drugs.